186k views
3 votes
Solve by completing the square:

x^2 + 2x - 3 =0
a. - 3 or 1
b. X-3 or -1
C. - 3 or -1
d. 2-3 or 1
Please select the best answer from the choices provided

1 Answer

1 vote

Answer:

a

Explanation:

Given

x² + 2x - 3 = 0 ( add 3 to both sides )

x² + 2x = 3

To complete the square

add ( half the coefficient of the x- term )² to both sides

x² + 2(1)x + 1 = 3 + 1

(x + 1)² = 4 ( take the square root of both sides )

x + 1 = ±
√(4) = ± 2 ( subtract 1 from both sides )

x = - 1 ± 2

Thus

x = - 1 - 2 = - 3

x = - 1 + 2 = 1

User Ojus Sangoi
by
5.5k points